Implementasi Program Menghafal Al-Qur'an Dengan Metode Sambung Ayat di Madrasah Aliyah Swasta Plus Al-Ulum Medan - Muttaqin, Imam; Rahman, Abd (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
The decline in students' motivation and effectiveness in memorizing the Qur'an raises concerns about the sustainability of traditional approaches in Islamic education. Although the tahfidz program is central in strengthening students' religiosity, existing practices are still partial, lack structured methods, and are not equipped with systematic evaluation. This indicates the urgency of developing innovative techniques that remain based on Islamic culture and can foster consistency, interest, and quality in students' memorization. This study aims to explore the implementation of the sambung ayat method in improving students' ability to memorize the Qur'an by examining the stages of planning, implementation, and evaluation applied in the school context. The research method uses a qualitative approach with a descriptive phenomenological design, conducted at MAS Plus Al-Ulum Medan in the 2025/2026 academic year. The research subjects were selected purposively, including teachers, students, and the head of the madrasah, who were directly involved in the tahfidz program. Data were obtained through semi-structured in-depth interviews, participant observation, and documentation studies. Data analysis followed Moustakas' phenomenological steps, while data validity was maintained through methodological and source triangulation. The results showed that the sambung ayat method significantly improved students' memorization fluency, as indicated by a reduction in errors and hesitations compared to before its implementation. Students were more enthusiastic and active, while a structured mechanism for monitoring progress assisted teachers. Weekly evaluations strengthened memory and provided constructive feedback. The verse-linking method offers a practical and empirical approach to optimizing Quran memorization. This study contributes by providing a conceptual and empirical basis for contextual, structured, and interactive tahfidz innovation while guiding the development of pedagogy and teacher training policies.